Formal Speciï¬cation and Documentation using Z - Bowen, Jonathan ([k.x.đ], 2003)
Bibliography: 253 - 283; Introduction (Formal Speciï¬cation using Z; Industrial Use of Formal Methods; A Brief Introduction to Z); Network Services (Documentation using Z; A File Storage Service); UNIX Software (A Text Formatting Tool; An Event-based Input System); Instruction Sets; Graphics; Window Systems;